Monitoring Data Analytics Segmentasi UMKM pada Kelurahan Semper Barat, Kecamatan Cilincing, Jakarta Utara Menggunakan Tableau Public - Lusi Noviani; Dea Zerlinda Ardini; Dinny Amalia Lestari; Tri Wahyudi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
UMKM is an abbreviation of the words Micro, Small and Medium Enterprises, describing economic activities carried out by individual, group, household or small businesses that are included in the standards as micro or medium enterprises. This activity can encourage independent abilities to develop in society, especially in the economic sector. With the existing problems, information media is needed to make it easier to search for information and a dashboard of developments in the number and sales results produced by West Semper Village UMKMs. The proposed solution is the use of information media via the Tableu website which can be used to monitor UMKMs in Semper Barat Subdistrict. This Tabblue dashboard produces a display in the form of values and narratives that can be accessed by the community, regional administrators and stake holders, to help them monitor and see how UMKMs have developed in the last 1 year. So it is hoped that the use of Tableu Information Media can have a good impact on the people of Semper Barat Village. So it is expected that the use of this Tableu Information Media can have a good impact on the people of Semper Barat Village. This Tableu is one of the Efforts in depicting real MSME information so that the Community knows that MSMEs are able to play a role as a supporter of life or family economic income that can be built from micro to medium with Efforts that are carried out consistently and sustainably.